Contribuição ao estudo de campo cristalino e transições 4f-4f em sistemas contendo lantanídeos - Souza, Adelmo Saturnino de (2012)
A theoretical study of the interactions between the 4f electrons in lanthanide ions (Ln3 +) with the chemical environment was made using crystal field theory. The main effects were studied: change in position of the berycentre of the energy levels of the free ion, maximum splitting of the J level and contribution to 5D0-7F0 transition of Eu3+ ion. Use of second-order correction to the wave functions allow a better understanding the relationship between the maximum splitting 7F1 Eu3+ ion and the position of its berycentre. The dependence between the intensity of the 5D0-7F0 transition with its position was also demonstrated using the linear part of the crystal field. This study was done based on symmetry properties of the Hamiltonian of the free ion and crystal field. The predicted position of the berycentre and the maximum splitting of the 7F1 level are in good agreement with the experimental results. The equations for the 5D0-7F0 transition satisfactorily reproduced the experimental data and can be used for the Sm2+ ion.